303 Mapping the Landscape of Surgical Registries in the United Kingdom. (28th February 2022) - Moore, C.; Avery, K.; Young, A.; Hinchliffe, R.; Potter, S.
Abstract: Introduction: Well-designed surgical registries are essential for high-quality patient-centred evaluation of implantable devices and surgical procedures. The importance of registries was highlighted in the recent Cumberlege report that detailed important innovation failures such as the use of vaginal mesh. Many surgical registries exist, but it is currently unclear how different registries are funded; designed; what data are collected; how databases are hosted and if the data can be linked to other datasets. There is therefore a need to understand the characteristics of and variation in existing surgical registries to make recommendations for how these could be improved. The aim of this work is to identify existing surgical registries in the UK and describe and summarise their key characteristics to inform recommendations for how surgical registries may be improved. Method: Existing surgical registries will be identified using multiple different sources, including society websites; search engine review; a targeted search of Medline and Embase databases and expert knowledge. Details of each registry will be extracted using a standardised data extraction proforma developed by the study team. Characteristics of identified registries will be summarised into a narrative review. Results: Identification of registries is ongoing. Preliminary data extraction has highlighted marked heterogeneity in the design, content, and structure of existing surgical registries. Data extraction is ongoing, but results will be available for presentation at the ASIT meeting. Conclusions: There is considerable heterogeneity in existing surgical registries. Further work is needed to establish the extent of this variation and identify areas that can be improved.